Public Sentiment towards the Medan-Binjai Water Pipeline Excavation using the Naïve Bayes Method - Turnip, Liana Tasya; Manurung, Hotler; Prahmana, I Gusti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The work on this project received sharp scrutiny from Non-Governmental Organizations (NGOs) because it was suspected that it was not in accordance with the Work Operation Standards (SOP) and not in accordance with the Technical Instructions (Guidelines for Implementation) and Juknis (Technical Instructions) .Naive Bayes is based on a simplified estimate that attribute values are conditionally independent of each other when given output values. Obtain an accuracy value of 0.75, with a negative precision classification of 0.75, negative recall1.00 f1-score negative0.86 and a negative3 support value. Precision classification Positive 0.00 positive recall 0.00 f1-score positive 0.00 and positive support value 1. This means that the performance of the system's success in retrieving information that has a positive value in the document is very low. -Binjai using the Naive Bayes algorithm method, it can be concluded as follows: 1) The accuracy level produced by the naïve Bayes classifier is 75%. 2) The advantages of this study are that it has good accuracy, precision and recall values, so that it is enough to be used in a system. 3) The deficiency in this research is in the performance of the system in finding the success of the system to find back information in the positive class, which is equal to 0.00%. This is because the amount of training data in the positive class is less than the negative class or it can be said that the training data used in this study is not balanced.